2014
DOI: 10.1242/dev.117804
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ signaling inhibits goblet cell differentiation via SPDEF in conjunctival epithelium

Abstract: The ocular surface epithelia, including the stratified but nonkeratinized corneal, limbal and conjunctival epithelium, in concert with the epidermal keratinized eyelid epithelium, function together to maintain eye health and vision. Abnormalities in cellular proliferation or differentiation in any of these surface epithelia are central in the pathogenesis of many ocular surface disorders. Goblet cells are important secretory cell components of various epithelia, including the conjunctiva; however, mechanisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…Klf4 and Klf5 mRNA levels were unchanged in microarray analysis of the conjunctiva of Spdef null mice [23], indicating that Klf4 and Klf5 function upstream of Spdef ( Figure 4A), while microarray analysis of the conjunctiva of Klf4 deficient mice showed a decrease in Spdef expression as well as of the winged-helix transcription factors Foxa1 (forkhead box A1) and Foxa3 [5]. Foxa3 and SPDEF mutually induce each other's expression in keratin 14-expressing cells in vitro [24].…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…Klf4 and Klf5 mRNA levels were unchanged in microarray analysis of the conjunctiva of Spdef null mice [23], indicating that Klf4 and Klf5 function upstream of Spdef ( Figure 4A), while microarray analysis of the conjunctiva of Klf4 deficient mice showed a decrease in Spdef expression as well as of the winged-helix transcription factors Foxa1 (forkhead box A1) and Foxa3 [5]. Foxa3 and SPDEF mutually induce each other's expression in keratin 14-expressing cells in vitro [24].…”
mentioning
confidence: 98%
“…One gene that is of special interest in goblet cell differentiation is sterile a motif pointed domain epithelial specific transcription factor (Spdef). SPDEF was originally described as a prostate-specific transcription factor [18,19], but has since been shown to play an integral role in goblet cell differentiation in the intestine [20,21], the lung [22], and the conjunctiva [23,24] (Box 1). However, upstream regulators of Spdef vary contextually or have not been tested globally, thus hindering a complete understanding of goblet cell differentiation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…After E16.5, eyelid growth was slowed during development in B6-Co mice, and the eyelids remained open even at P0 (Figure 1E-H). It has been reported that the best time for eyelid closure is about E16.5, at which time the cornea and other eye accessory structures involved in gradual development could interfere with fusion of the upper and lower eyelids (McCauley et al, 2014;Heude et al, 2015). The eyelids of B6-Co mice grew slowly, and therefore missed the ideal period for eyelid fusion, demonstrating temporal and spatial specificity in embryonic development.…”
Section: Gene Namementioning
confidence: 99%